2016
DOI: 10.2139/ssrn.2805342
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Urban Mobility: Integrating Ride-Sharing and Public Transit

Abstract: Seamless integration of ride-sharing and public transit may offer fast, reliable, and affordable transfer to and from transit stations in suburban areas thereby enhancing mobility of residents. We investigate the potential benefits of such a system, as well as the ride-matching technology required to support it, by means of an extensive computational study. 1 Introduction People all around the world use private cars to travel to work. Most of these commuter trips are singleoccupant vehicle trips. In the U.S., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Stiglic et al. () investigated the benefits of integrating ride‐sharing services and public transit and showed that such integrated system can significantly enhance mobility and increase the use of public transport.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stiglic et al. () investigated the benefits of integrating ride‐sharing services and public transit and showed that such integrated system can significantly enhance mobility and increase the use of public transport.…”
Section: Literature Reviewmentioning
confidence: 99%